Analisis Pengaruh Servicescape Terhadap Kepuasan Pelanggan di Prima Freshmart Sekolah Vokasi IPB University - Az Zahra, Nabila Rahmania; Farelia Amarnita Putri; Marcella Magdhalena Erlely; Kayla Nuzulul Fitri; Sephia Anggira Putri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research explores how service quality (servicescape) at Prima Freshmart, Sekolah Vokasi IPB University, affects customer satisfaction. Researchers surveyed 100 customers to gauge their perceptions of service quality and satisfaction. The results indicate that servicescape, as a whole, positively influences customer satisfaction. Among the servicescape dimensions, attentiveness and reliability emerged as the most influential. This suggests that customers value caring and dependable attitudes from the staff at Prima Freshmart. In conclusion, servicescape is a crucial factor for Prima Freshmart to consider in boosting customer satisfaction. Management should prioritize enhancing service quality, particularly regarding staff attentiveness and reliability, to cultivate a more satisfied customer base and encourage repeat business at Prima Freshmart.